1991
DOI: 10.1111/j.1471-0528.1991.tb13508.x
|View full text |Cite
|
Sign up to set email alerts
|

Doppler investigation of uteroplacental blood flow resistance in the second trimester: a screening study for pre‐eclampsia and intrauterine growth retardation

Abstract: Objective-To assess the screcning propertics of a mid-trimester uteroplacental Doppler scan in a normal unselectcd population. Design-A cross-sectional study measuring an averaged resistance index (AVRI) from four sites (left and right uterine and arcuate arteries) with continuous wave Doppler ultrasound. Setting-Rout ine booking ultrasound, King's College Hospital, London. Subjects-977 women at 16-24 weeks gestation. Mairi outcome measures-Intrauterine death, birthweight, pregnancy-induced hypertension (PIH),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
120
1
9

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(144 citation statements)
references
References 28 publications
14
120
1
9
Order By: Relevance
“…The association between abnormal uterine artery Doppler FVW and measures of bad obstetric outcome (PET, LBW and perinatal death) is in keeping with other studies 12,18,23,24 . Abnormalities of uterine artery Doppler FVW, persisting after 24 weeks of gestation, are predictive of subsequent pregnancy complications, including PET and IUGR 12,25 .…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The association between abnormal uterine artery Doppler FVW and measures of bad obstetric outcome (PET, LBW and perinatal death) is in keeping with other studies 12,18,23,24 . Abnormalities of uterine artery Doppler FVW, persisting after 24 weeks of gestation, are predictive of subsequent pregnancy complications, including PET and IUGR 12,25 .…”
Section: Discussionsupporting
confidence: 72%
“…All Doppler FVW were either printed, or recorded on video. Abnormal uterine artery Doppler FVW ≥ 24 weeks were defined as bilateral/ ipsilateral early diastolic notches, or a mean /ipsilateral uterine artery RI value ≥ 0.58 12,18 . Notched or high resistance Doppler FVW prior to 24 weeks of gestation were not considered abnormal, since trophoblast invasion and transformation of the maternal vasculature may continue between 20 and 24 weeks of gestation in some normal pregnancies.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to placental size several factors influence fetal growth including placental blood flow [2][3][4][5] , maternal height and weight [6][7][8] and maternal smoking habits. To investigate a complex system it is first necessary to look at its parts.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15] Other studies have indicated the utility of color Doppler sonography for the assessment of placenta accreta and the identification of vasa previa. 16,17 The current study shows that the administration of Levovist enhances the color Doppler signal of the placenta.…”
Section: Discussionmentioning
confidence: 99%